Marketing underutilized plant species for the benefit of the poor: a conceptual framework - Gruère, Guillaume P.; Giuliani, Alessandra; Smale, Melinda (International Food Policy Research Institute, 2006)
Modern crop production is based on only a few plant species. Particularly in marginal environments of developing agricultural economies, many less well-known agricultural or non-timber forest species, continue to be grown, managed or collected, thus contributing to the livelihood of the poor and to agricultural biodiversity. Some of these species, called underutilized plant species, are characterized by the fact that they are locally in developing countries but globally rare, that scientific information and knowledge about them is scant, and that their current use is limited relative to their economic potential. In this paper, we first identify the economic factors that cause these plants to be ‘underutilized’. Based on this analysis, we propose a classification of underutilized plant species based on the relationship of the observed to the potential economic value of the species, and the presence or absence of and constraints to output markets. Then, focusing on a subset of underutilized plant species with market potential, we identify three necessary conditions for the successful commercialization of underutilized plant species for the benefit of the poor: demand expansion, increased efficiency of supply and marketing channels, and a supply control mechanism. This conceptual framework is intended to provide a basis for an empirical assessment of marketing solutions for underutilized plant species among the rural poor in developing economies.